Synaptic enrichment of pSer129 alpha-synuclein correlates with dopaminergic denervation in early-stage Parkinson’s disease - Irene Frigerio; Martino L. Morella; Amber B. Winkelaar; Danai T. Vorgia; John JP Brevé; Walter A. Boiten; Bram L. van der Gaag; Ismael L. Calandri; Allert J. Jonker; Henk W. Berendse; Daniel Mona; Markus Britschgi; et al. (Nature Communications)
Abstract In Parkinson’s disease (PD), α-synuclein aggregation in striatal synapses is hypothesised to trigger a cascade of events leading to synaptic loss and cortical Lewy body (LB) pathology. Using multiplex immunofluorescence and confocal microscopy on 69 brains spanning Braak stages 0–6—including controls, incidental LB disease (iLBD), and PD—we show that phosphorylated (pSer129) α-synuclein is enriched in putaminal dopaminergic synapses already in early disease stages, and associates with dopaminergic terminal loss. C-terminally truncated (CTT122) α-synuclein shows a similar trend in later stages. Enrichment of pSer129 and CTT122 α-synuclein in cortical glutamatergic synapses in the putamen occurs prior to LB appearance in cortical regions, supporting the theory of α-synuclein retrograde transport from synapse to cell body. Using AlphaLISA, we confirm that isolated PD putaminal synaptosomes contain higher pSer129 α-synuclein protein levels compared to controls. These findings suggest that synaptic enrichment of pSer129 α-synuclein occurs in early PD, possibly contributing to dopaminergic denervation and cortical LB pathology.